Correlation between plasma fibrinogen levels and microvascular complications in type 2 diabetes - Hamidullah; Ahmad, Ishtiaq; Ashraf; Ali, Murad; Hussain, Manzoor; Zakirullah (Journal of the Pakistan Medical Association, 2024)
Objective: To determine how plasma fibrinogen levels impact the severity of microvascular complications in people with type 2 diabetes while focussing on the molecular mechanisms of fibrinogen’s role in such complications. Method: The analytical, cross-sectional study was conducted from September 2022 to March 2023 at the Department of Medicine, Mardan Medical Complex and Teaching Hospital, Khyber Pakhtunkhwa, Pakistan, and comprised adult patients of either gender who had been diagnosed with type 2 diabetes and microvascular complications. Each patient was subjected to an evaluation of microvascular complications, including diabetic retinopathy, nephropathy and neuropathy, using validated diagnostic criteria and clinical examinations. Data was analysed using SPSS 26. Results: Of the 174 patients 97(%) were males and 77(%) were females. Retinopathy was found in 57(32.7) patients with median age 53 years (interquartile range: 46-63 years). Nephropathy was found in 55(31.6%) subjects with median age 54 years (interquartile range: 50-61 years). Neuropathy was found in 62(35.6%) patients with median age 53 years (interquartile range: 48-58 years). Diabetic neuropathy was significantly associated with elevated plasma fibrinogen levels and various biomarkers, such as creatinine, urea, fasting blood glucose, glycated haemoglobin and estimated average glucose (p<0.05). Diabetic retinopathy was significantly linked with higher levels of fibrinogen, which manifested through symptoms, like floaters or dark spots, impaired colour vision, difficulty seeing at night, blurred or fluctuating vision and vision loss (p<0.05). Diabetic nephropathy and the progression of its severity was significantly associated with increased fibrinogen levels, as well as markers, like albuminuria, creatinine, urea, fasting blood glucose, glycated haemoglobin and estimated average glucose (p<0.05). Conclusion: Elevated plasma fibrinogen levels in patients with type 2 diabetes significantly correlated with increased microvascular complications, underscoring the importance of monitoring and managing fibrinogen levels to mitigate diabetes-associated vascular pathologies. Key Words: Diabetes mellitus, Microvascular complications, Serum fibrinogen, Nephropathy, Retinopathy, Neuropathy.